Copper-containing mesoporous bioactive glass promotes angiogenesis in an in vivo zebrafish model - Romero-Sánchez, Lilian B.; Mari-Beffa, Manuel; Carrillo Fernández, Paloma; Medina-Torres, Miguel Ángel; Díaz-Cuenca, Aránzazu (My University, 2018)
The osteogenic and angiogenic responses of organisms to the ionic products of degradation of bioactive glasses (BGs) are being intensively investigated. The promotion of angiogenesis by copper (Cu) has been known for more than three decades. This element can be incorporated to delivery carriers, such as BGs, and the materials used in biological assays. In this work, Cu-containing mesoporous bioactive glass (MBG) in the SiO2-CaO-P2O5 compositional system was prepared incorporating 5% mol Cu (MBG-5Cu) by replacement of the corresponding amount of Ca. The biological effects of the ionic products of MBG biodegradation were evaluated on a well-known endothelial cell line, the bovine aorta endothelial cells (BAEC), as well as in an in vivo zebrafish (Danio rerio) embryo assay. The results suggest that ionic products of both MBG (Cu free) and MBG-5Cu materials promote angiogenesis. In vitro cell cultures show that the ionic dissolution products of these materials are not toxic and promote BAEC viability and migration. In addition, the in vivo assay indicates that both exposition and microinjection of zebrafish embryos with Cu free MBG material increase vessel number and thickness of the subintestinal venous plexus (SIVP), whereas assays using MBG-5Cu enhance this effect.
Keywords: Neovascularización; Bioactive glass; Zebrafish; Angiogenesis